Implementation of a 3D Virtual Learning Environment (MATHLIFE) Including Daily Life Activities in Mathematics: Experiences and Difficulties - Selahattin Arslan, Mesut Bütün, Tuba Gökçek, Gönül Güneş, Orhan Çakıroğlu, Bahar Baran, Serkan Coştu (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2017)
Three-dimensional (3D) virtual learning environments, which have become increasingly popular in recent years, have a strong potential to facilitate the learning of students. In the case of mathematics which has difficulties in learning and teaching, it is important to evaluate this potential in detail in different dimensions. The aim of this study is to examine the experiences and emerging challenges in the application process of the 3D virtual learning environment that requires mathematical skills. A 3D virtual learning environment (Mathlife), which requires math skills, was designed and applied to students in different profiles (discalkulic, normal, gifted). A total of 20 students, selected from 4th (10 students) and 7th (10 students) grade, participated in the study. A semi-structured observation form was used as data collection tool. This form consists of 5 open-ended questions asking the participating researchers to evaluate the environment in different dimensions. The findings of the study revealed that, in general, the implementation process can be carried out as planned and that the designed environment presents a rich mathematics learning context for students, even though differences sometimes may occur. Also, it has been determined that some difficulties can be experienced in the study, especially the technical problems during the implementation process, and some of these difficulties are eliminated as the process progresses. As a result of the study, recommendations for studies which are planned to be carried out in the future has been presented.